Drawing lots from egalitarianism to democracy in ancient Greece - Malkin, Irad 1951-; Blok, Josine 1953- (Oxford University Press, 2024)
"This book offers the first comprehensive study of drawing lots as a central institution of ancient Greek society. It reveals how an egalitarian mindset guided selection, procedure, and distribution by lot and how drawing lots was introduced for polis governance, a Greek innovation that may be relevant today. The first two parts (Irad Malkin) explore the egalitarian mindset geared towards horizontal relationships, expressed in drawing lots instead of a top-down vision of authority and sovereignty. Drawing lots presupposes equality among participants deserving equal "portions" and was used for distributing land, inheritance, booty, sacrificial meat, selecting individuals, setting turns, mixing, and reorganizing groups, and divining the will of the gods. It was a self-evident method broadly applied. Drawing lots crystallized community boundaries and emphasized its sovereignty. The guiding values were equality and fairness. The gods were the guardians of the just procedure of drawing lots, but they did not predetermine the outcome. The third part (Josine Blok) investigates the transposition of the drawing of lots to the governance of the polis. The implied egalitarianism was often in conflict with a top-down perception of society and the values of inequality, status, and merit. Drawing lots was introduced into oligarchies and democracies at an uneven pace and scale. Its use in the democracy of classical Athens was an exceptional case, eye-catching both in antiquity and today. Conclusions about the meaning of the Greek examples for drawing lots today and an appendix (Elena Iaffe) surveying the Greek vocabulary of drawing lots close the book."